1977
DOI: 10.2151/jmsj1965.55.2_174
|View full text |Cite
|
Sign up to set email alerts
|

Reflection of Solar Radiation from an Array of Cumuli

Abstract: The solar radiation reflected by an array of finite broken clouds corresponding to cumuli is examined. The importance of the distribution of cloud size is demonstrated by using the actual cloud pattern over Florida. The accuracy of simplified cloud models (plane-parallel infinite cloud or an array of identical clouds) to approximate the array of clouds with size distribution is examined. The result shows the following: (1) The model of plane-parallel infinite cloud causes fairly large error in the reflection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…As Snow (1985) and Minnis (1989) show, clouds in broken cloud fields appear to occupy increasing portions of a scene as it is viewed from increasingly oblique angles. The cloud fraction apparent from the sun's direction (CF app ) has been used in numerous radiative studies (e.g., Aida 1977;Kobayashi 1988;Barker 1994). The TIPA is closely related to this CF app since both calculate the fraction of the incoming solar radiation that is intercepted by clouds, but TIPA extends the concept of the CF app , which distinguishes only between cloud and no cloud, by also accounting for variations in cloud optical thickness.…”
Section: Fig 3 (A)mentioning
confidence: 99%
See 1 more Smart Citation
“…As Snow (1985) and Minnis (1989) show, clouds in broken cloud fields appear to occupy increasing portions of a scene as it is viewed from increasingly oblique angles. The cloud fraction apparent from the sun's direction (CF app ) has been used in numerous radiative studies (e.g., Aida 1977;Kobayashi 1988;Barker 1994). The TIPA is closely related to this CF app since both calculate the fraction of the incoming solar radiation that is intercepted by clouds, but TIPA extends the concept of the CF app , which distinguishes only between cloud and no cloud, by also accounting for variations in cloud optical thickness.…”
Section: Fig 3 (A)mentioning
confidence: 99%
“…This approach is different from the one used in previous studies, which focused on how heterogeneities influence the radiation field at various fixed locations. For example, Davis (1992), Marshak et al (1995a), Gabriel and Evans (1996), Davis et al (1997), and Chambers et al (1997) examined the radiation at points of various densities within a cloud with volume extinction coefficient variations; and McKee and Cox (1974), Davies (1976Davies ( , 1978, Aida (1977), Welch and Wielicki (1984), and Bréon (1992) studied the radiation that left cuboidal and cylindrical clouds through their tops and, separately, their sides. The difference between the present approach and other ones is analogous to the difference between the Lagrangian and Eulerian approaches used, for example, in fluid dynamics.…”
Section: Calculation Of Heterogeneity Effects a General Approachmentioning
confidence: 99%
“…The effect of three-dimensional (3D) cloud variability on the transport of solar flux in the atmosphere has been an active area of research for the last three decades (e.g., McKee and Cox 1974;Aida 1977;Davies 1978;Harshvardhan and Thomas 1984;Welch and Wielicki 1984;Barker and Davies 1992;Cahalan et al 1994b;Marshak et al 1995b;Barker et al 1998;O'Hirok and Gautier 1998;Zuidema and Evans 1998;Benner and Evans 2001;Scheirer and Macke 2003;Di Giuseppe and Tompkins 2005). The 3D radiative transfer effect on domain-averaged solar fluxes has been divided into two physical processes, as summarized by Várnai and Davies (1999).…”
Section: Introductionmentioning
confidence: 99%
“…Cloud field radiative fluxes have been modeled by Aida [1977], Claussen [1982], Welch and Wielicki [1984,1989], Zuev et al [1987], Kobayashi [1989], and others. Cloud shape, mutual shadowing, cloud-cloud interactions, spatial inhomogeneities, and surface albedo have been demonstrated to be important variables.…”
Section: Introductionmentioning
confidence: 99%
“…Most three-dimensional radiation models have assumed uniform cloud spacing. However, Aida [1977] and Kite [1987] have demonstrated that radiative fluxes are sensitive to cloud-size and spatial distributions. Clearly, cloud inhomogeneities and cloud spatial patterns are important variables.…”
Section: Introductionmentioning
confidence: 99%